Green and Low Carbon Development Performance in Farmland Use Regulation: A Case Study of Liyang City, China - Yaoben Lin; Xuewen Wang; Guangyu Li; Wei Shen (Land)
Farmland use regulation strictly regulates the conversion of agricultural land for other agricultural purposes and the construction of agricultural facilities, thereby optimizing the land use pattern in rural areas. However, different measures and intensities of farmland use regulation can affect the overall performance of green and low-carbon development in rural areas. This study utilizes system dynamics modeling and simulation to conduct a case study based on current land use data from 10 towns in Liyang City, China. The empirical results indicate the following: (1) Based on comprehensive measurements of green and low carbon development performance, Liyang City exhibits a pattern of higher indices in the south and lower indices in the north. Towns such as Tianmu Lake, Daibu, and Shezhu show relatively high average comprehensive indices of 0.31, 0.30, and 0.28, significantly higher than other towns. (2) Simulation of farmland use regulation’s impact on green and low carbon development performance reveals that Scenario One, involving additional construction land occupying farmland, achieves a comprehensive index of only 0.23, significantly lower than the other scenarios. (3) Based on calculations and field surveys, Liyang City’s villages are categorized into four types, with the largest number being industry-integrated villages (94 villages). Accordingly, policies for farmland use regulation are designed for different village types. Therefore, future farmland use regulation should be tailored with differentiated institutional designs according to the development needs of different villages. This study’s findings provide insights into green and low-carbon development in rural areas.